Impedance studies of proton conducting plasticized polymer electrolyte based on starch - Khiar, A.S.A.; Arof, Abdul Kariem (2009)
In the present work, plasticized polymer electrolytes based on starch has been prepared by solution casting technique. The conductivity of the films has been characterized using impedance spectroscopy at various frequencies and temperatures. The impedance plot for the films containing 4 wt. % of glycine consists of a spike at the low frequency end of the plot and th conductivity obtained at room temperature was (8.55 ± 0.89) x 10-5 Scm-I. The temperature-dependent conductivity data obeys Arrhenius relationship. The dielectric constant increased with the increase in temperature and decreased with the increase in frequency.